PENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN STRATEGI PEMBELAJARAN BERBASIS MASALAH DI SEKOLAH DASAR - Randi Eka Putra (Program Studi Teknologi Informasi, Universitas Muhammadiyah Muara Bungo, 2021)
Abstract — This background of the research is bad value of mathematics learning of class IV elementaray school 60/II Muara Bungo. It because convesional learning, students are nothing in the learning process, problem base learning strategy is useless in the learning. Research method is classroom action reseacrh with qualitative and quantitative. Research subject in the class IV elementary school 60/II Muara Bungo the students are 30 in the classroom. In the action of this researh, there are 2 the circulating do by the reseacher. There are 4 action from every circulate that is action of planning, action of implementation, observation, and reflection each circulating. This research data is collected by observation, learning value, and documentation. Research value shows 1) the using props as simple unit of weight with demonstration method increase teacher and students process. Teacher process of first circulating increase about 81% (very good) and the second circulating increase about 91% (excelent). The students activity of first circulating increase about 84% (very good) and the second circulating increase about 90% (excelent). 2) improving learning value get a good grade of minimal completeness criteria (65) with pre circulating percentage 51%, first circulating 60%, and second circulating 76%.